Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Field test of a scaled-up bioelectrochemical sequential reductive/oxidative process for chlorinated aliphatic hydrocarbons (CAHs) remediation from contaminated groundwater - Edoardo Dell'Armi; Paolo Ciampi; Angela Marchetti; Ernst Bartsch; Marcel Alesi; Eduard J. Alesi; Gert Rehner; Bruna Matturro; Viktoria Feigl; Monika Molnar; Simona Rossetti; Marco Petrangeli Papini; et al. (Chemical Engineering Journal, 2025)

A geophysical multidisciplinary approach to investigate the shallow subsoil structures in volcanic environment: The case of Ischia Island - Lucia Nardone; Maurizio Vassallo; Giovanna Cultrera; Vincenzo Sapia; Simona Petrosino; Marta Pischiutta; Mauro Di Vito; Sandro de Vita; Danilo Galluzzo; Giuliano Milana; Eliana Bellucci Sessa; Antonella Bobbio; et al. (Journal of Volcanology and Geothermal Research, 2023)

Relationship of long-term air pollution exposure with asthma and rhinitis in Italy: an innovative multipollutant approach - Sara Maio; Salvatore Fasola; Alessandro Marcon; Anna Angino; Sandra Baldacci; Maria Beatrice Bilò; Roberto Bono; Stefania La Grutta; Pierpaolo Marchetti; Giuseppe Sarno; Giulia Squillacioti; Ilaria Stanisci; et al. (Environmental Research, 2023)

Evaluation of three commercial assays for SARS-CoV-2 molecular detection in upper respiratory tract samples - Flora Marzia Liotti; Giulia Menchinelli; Simona Marchetti; Grazia Angela Morandotti; Maurizio Sanguinetti; Brunella Posteraro; Paola Cattani (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The increasing COVID-19 widespread has created the necessity to assess the diagnostic accuracy of newly introduced (RT-PCR based) assays for SARS-CoV-2 RNA detection in respiratory tract samples. We compared the results of the Allplex™ 2019-nCoV assay with those of the Simplexa™ COVID-19 Direct assay and the Quanty COVID-19 assay, respectively, all performed on 125 nasal/oropharyngeal swab samples of patients with COVID-19 suspicion. Fifty-four samples were positive, and 71 were negative with the Allplex™ assay, whereas 47 of 54 samples were also positive with the Simplexa™ assay. The Quanty assay detected 55 positive samples, including the 54 positive samples with the Allplex™ assay and 1 sample that was Allplex™ negative but Simplexa™ positive. Using a consensus result criterion as the reference standard allowed to resolve the eight samples with discordant results (one Allplex™ negative and seven Simplexa™ negative) as truly false negative. Interestingly, a Spearman’s negative association was found between the viral RNA loads quantified by the Quanty assay and the C T values of RT PCRs performed with either the Allplex™ assay or the Simplexa™ assay. However, the strength of this association was higher for the Allplex™ assay (N gene, ρ = − 0.92; RdRP gene, ρ = − 0.91) than for the Simplexa™ assay (ORF1ab gene, ρ = − 0.65; S gene, ρ = − 0.80). The Allplex™ 2019-nCoV, the Simplexa™ COVID-19 Direct, and the Quanty COVID-19 assays yielded comparable results. However, the role these assays might play in future clinical practice warrants larger comparison studies.

Therapeutic potential of MEK inhibition in acute myelogenous leukemia: rationale for “vertical” and “lateral” combination strategies - Maria Rosaria Ricciardi; Maria Cristina Scerpa; Paola Bergamo; Ludovica Ciuffreda; Maria Teresa Petrucci; Sabina Chiaretti; Simona Tavolaro; Maria Grazia Mascolo; Stephen L. Abrams; Linda S. Steelman; Twee Tsao; Antonio Marchetti; et al. (Journal of Molecular Medicine, 2012)